PENERAPAN PENDEKATAN METAKOGNITIF DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA SMA PADA MATERI GERAK HARMONIK SEDERHANA - Dewi Yulianawati; Hera Novia; Iyon Suyana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Problem solving ability should be owned by students in high school after studying the physics concept, because physics subject is important role in the development of science and technology. In other words, physics subject as one of the capital bases to create the human resources  in order to face 21st century. Preliminary studies that conducted in one of the High School in Bandung, students face the difficulties to solve the problems. One of the students who didn’t know what they have to do. As concequency,  required to involve metacognitive in physics learning. The purpose of the research is to find out the enhancement physics problem solving abilities after metacognitive approach learning had been conducting. This study was conducted for three times for  32 students at one class in one of the high school in Bandung with research method is quasi experimental design and Pre-test and Post-test Group research design. The instrument is used to measure problem-solving ability that consist of two essay with stages by Heller. The results show that metacognitive approach learning be able enhance every aspect of physics problem-solving ability with N-Gain increase by 0,45 in the medium category. The enhancement of focus the problem aspects’, plan a solution aspects’, and execute the plan aspects’ in the medium category. Whereas to describe the physics aspects’ and evaluating answers aspects’ in the low category. Thus, it can be concluded that the metacognitive approach to learning be able enhance highschools’ physics  problem solving abilities.Keywords: Metacognitive Approach, Physics Problem Solving